Does New WHO 2022 Nomenclature of Pituitary Neuroendocrine Tumors Offer an Extra Edge to the Neurosurgeons for Its Management? A Narrative Review - Srivastava, Alok; Singh, Manish; Yadav, Awadhesh; Srivastava, Chhitij; Chandra, Anil; Srivastava, Akanksha D. (Asian Journal of Neurosurgery, 2024)
The new World Health Organization nomenclature of pituitary tumors was introduced in the year 2022 after much deliberation. This nomenclature clearly demarcates the anterior lobe (adenohypophyseal), posterior lobe (neurohypophyseal), and hypothalamic tumors. There is also focus on other tumors arising in the sellar region. The nomenclature has also advocated the routine use of immunohistochemistry in describing the pituitary transcription factors that plays a fundamental role in distinguishing the cell lineage of these tumors. However, the nomenclature is complex in understanding due to inclusion of pathological correlates like transcription factors, hormones, biomarkers, and various controversies that have emerged regarding the renaming of pituitary adenomas (PA) as PiTNETs (“Pituitary Neuroendocrine tumors”) because majority of the adenomas are benign and have rare metastatic behavior while classifying them as PiTNETs will create unnecessary misinterpretation of these as aggressive tumors that will lead to apprehension among the patients. The new classification gives deeper insight into the histological picture of the various pituitary tumors but other than contributing to the follow-up strategy and postsurgery management, this classification does not add anything new that could be advantageous for the neurosurgeons in clinical practice and decision making, especially in deciding the plan of action for surgery. Hence, there is need of a more comprehensive, integrated, neuroradiological-based classification with more emphasis on the invasiveness of these tumors that would assist the neurosurgeons in planning the treatment strategy and managing patients of pituitary tumors.
Keywords: pituitary tumors; PiTNETs; WHO classification; management; pituitary adenomas